Single Donor‐Derived Strongyloidiasis in Three Solid Organ Transplant Recipients: Case Series and Review of the Literature. Issue 5 (10th March 2014) - Le, M.; Ravin, K.; Hasan, A.; Clauss, H.; Muchant, D. G.; Pasko, J. K.; Cipollina, G.; Abanyie, F.; Montgomery, S. P.; Loy, M.; Ahmed, M.; Mathur, M.; et al.
<x xml:space="preserve">Abstract</x> Donor‐derived Strongyloides stercoralis infections in transplant recipients are a rare but recognized complication. In this case series, we report donor‐derived allograft transmission of Strongyloides in three solid organ transplant recipients. Following detection of infection in heart and kidney–pancreas recipients at two different transplant centers, a third recipient from the same donor was identified and diagnosed. S. stercoralis larvae were detected in duodenal aspirates, bronchial washings, cerebrospinal fluid, urine and stool specimens. Treatment with ivermectin and albendazole was successful in two of the three patients identified. The Centers for Disease Control and Prevention was contacted and performed an epidemiologic investigation. Donor serology was strongly positive for S. stercoralis antibodies on retrospective testing while all pretransplant recipient serum was negative. There should be a high index of suspicion for parasitic infection in transplant recipients and donors from endemic regions of the world. This case series underscores the need for expanded transplant screening protocols for Strongyloides. Positive serologic or stool tests should prompt early treatment or prophylaxis in donors and recipients as well as timely notification of organ procurement organizations and transplant centers.